2019
DOI: 10.1038/s41598-019-51177-x
|View full text |Cite
|
Sign up to set email alerts
|

Dewatering Behavior of a Wood-Cellulose Nanofibril Particulate System

Abstract: The novel use of aqueous suspensions of cellulose nanofibrils (CNF) as an adhesive/binder in lignocellulosic-based composite manufacture requires the removal of a considerable amount of water from the furnish during processing, necessitating thorough understanding of the dewatering behavior referred to as “contact dewatering”. The dewatering behavior of a wood-CNF particulate system (wet furnish) was studied through pressure filtration tests, centrifugation, and characterization of hard-to-remove (HR) water, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…30 CNF is reported to have a potential application as a binder. 31 Dewatering procedures have also been studied focusing on the use of CNF as a binder to other cellulosic particles, 32,33 and the application of CNF to reinforce natural fiber yarns. 34 Spraydried CNF is reported to replace conventional polyols by Leng et al 35 A high amount of CNF (40% polyol substitute or 20% loading level) is reported to disrupt cell structure while improving the cross-linking of CNF-PU and increasing compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…30 CNF is reported to have a potential application as a binder. 31 Dewatering procedures have also been studied focusing on the use of CNF as a binder to other cellulosic particles, 32,33 and the application of CNF to reinforce natural fiber yarns. 34 Spraydried CNF is reported to replace conventional polyols by Leng et al 35 A high amount of CNF (40% polyol substitute or 20% loading level) is reported to disrupt cell structure while improving the cross-linking of CNF-PU and increasing compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…The mixture was placed into a 3D-printed acrylonitrile butadiene styrene (ABS) mold which was then placed on a wire mesh. During this step, clear water was drained due to contact dewatering [37]. The solids content prior to drying was approximately 10 wt.%.…”
Section: Methodsmentioning
confidence: 99%
“…The dewatering behavior of CNFs mixed with wood particles of different sizes or specific surface areas was investigated [ 247 ]. Results showed that dewatering rate by pressure filtration of CNFs mixed with wood particles was significantly improved using particles with high specific surface area compared with pure CNFs alone.…”
Section: Drying and Dewatering Of Cellulosic Nanomaterialsmentioning
confidence: 99%